2017
DOI: 10.1194/jlr.m071340
|View full text |Cite
|
Sign up to set email alerts
|

Using primary murine intestinal enteroids to study dietary TAG absorption, lipoprotein synthesis, and the role of apoC-III in the intestine

Abstract: The intestine plays a crucial role in regulating wholebody lipid homeostasis through dietary fat absorption and secretion, and through its endocrine secretions of incretin hormones and immune mediators. The intestine synthesizes a specialized lipoprotein, the chylomicron, which contains both dietary triglyceride (TAG) and cholesterol, in addition to both structural and functional apolipoprotein cargo. apoB-48 provides structure to the nascent chylomicron, while apoA-IV, apoA-I, and apoC-III function in the per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 51 publications
(56 reference statements)
1
35
0
Order By: Relevance
“…To determine how intestinal apoC-III is regulated, we utilized a primary intestinal enteroid culture system. Primary enteroids are derived from WT mouse duodenal and jejunal crypt stem cells, and we have previously established that this tissue culture system significantly improves upon Caco-2 cells as a model for dietary fat absorption and chylomicron secretion [16]. In Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…To determine how intestinal apoC-III is regulated, we utilized a primary intestinal enteroid culture system. Primary enteroids are derived from WT mouse duodenal and jejunal crypt stem cells, and we have previously established that this tissue culture system significantly improves upon Caco-2 cells as a model for dietary fat absorption and chylomicron secretion [16]. In Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Because we have identified a unique consequence of apoC-III overexpression in the intestine (the inhibition of dietary fat absorption coupled with altered chylomicron secretion) [15,16], and because regulation of apoC-III in Caco-2 cell culture is so far removed from in vivo conditions that might regulate apoC-III, we wanted to establish the critical dietary factors in the regulation of intestinal apoC-III.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Enteroids have also been employed in a mitochondrial function study that demonstrated that the replacement of glucose with galactose increased crypt formation, differentiation, and mitochondrial activation . Of particular interest is the finding that metabolites (in particular butyrate) induced or produced by intestinal microbiota are able to inhibit colonic epithelial stem and progenitor proliferation . Basak et al.…”
Section: Enteroids As Models In Nutrition‐focused Studiesmentioning
confidence: 99%